2019
DOI: 10.1002/jcp.29229
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Akt2/PKBβ is involved in blastomere proliferation of preimplantation mouse embryos

Abstract: Activation of Akt/Protein Kinase B (PKB) by phosphatidylinositol-3-kinase (PI3K) controls several cellular functions largely studied in mammalian cells, including preimplantation embryos. We previously showed that early mouse embryos inherit active Akt from oocytes and that the intracellular localization of this enzyme at the two-cell stage depends on the T-cell leukemia/lymphoma 1 oncogenic protein, Tcl1.We have now investigated whether Akt isoforms, namely Akt1, Akt2 and Akt3, exert a specific role in blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This matches with the study of Chong et al that showed an enhancement of neural cell survival following administration of NAM under anoxia conditions through activating the AKT signaling that consequently reduced apoptosis [53]. Moreover, PI3K/AKT/mTOR signaling has a significant role in the development, metabolism, and pluripotency fate of cells [22,24,25] via modulating different transcription factors such as OCT4, SOX2, GATA4 and GATA6 [34,35]. OCT4 is the master controller of lineage specification of ICM [54] and for embryonic lineage-specific markers including SOX2 and GATA6.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This matches with the study of Chong et al that showed an enhancement of neural cell survival following administration of NAM under anoxia conditions through activating the AKT signaling that consequently reduced apoptosis [53]. Moreover, PI3K/AKT/mTOR signaling has a significant role in the development, metabolism, and pluripotency fate of cells [22,24,25] via modulating different transcription factors such as OCT4, SOX2, GATA4 and GATA6 [34,35]. OCT4 is the master controller of lineage specification of ICM [54] and for embryonic lineage-specific markers including SOX2 and GATA6.…”
Section: Discussionsupporting
confidence: 88%
“…SIRT1 exhibits its cellular activities via the transcription of various enzymes and signaling pathways including serine/threonine-specific protein kinase B (AKT) and mTOR [ 19 ]. On the other hand, the phosphatidylinositol 3-kinase (PI3K) and its downstream effectors AKT and mTOR regulate various cellular processes including apoptosis, development, proliferation, survival, and maintenance of pluripotency of embryos and stem cells [ 22 , 23 , 24 , 25 , 26 ]. PI3K mediates the activation of AKT at the Thr308 phosphorylation site via recruitment of phosphoinositide dependent kinase 1 (PDK1), whereas PDK1 can indirectly activate AKT at the Ser473 phosphorylation site by activating the rictor–mTOR complex 2 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PI3K/AKT pathway can mediate cell growth and survival in pre-implantation embryos. In early mouse embryos, PI3K-Akt subunits are expressed from zygote to blastocyst stage and are involved with blastomere proliferation (75,76). In bovine pre-implantation embryos, the activation PI3K signaling is also required for apoptosis control (71).…”
Section: Discussionmentioning
confidence: 99%
“…However, some non-differential genes may also be involved in the key biological activities of cells and play important roles in embryonic development [50] , [51] . As illustrated by functional analysis, the up-regulated expression of some key genes in MAPK and PI3K/Akt signaling pathways, both of which are essential for cell proliferation and differentiation [52] , [53] , results from the synergy of dark genes and their downstream targets. Thus, some dark genes such as IGF1 encoding growth factor and LAMC2 and COL4A1 encoding ECM are identified as upstream regulators for cell proliferation and may also be involved in other development processes.…”
Section: Discussionmentioning
confidence: 99%